1995
DOI: 10.2307/1940709
|View full text |Cite
|
Sign up to set email alerts
|

Cold Hardiness and Overwintering Strategies of Hatchlings in an Assemblage of Northern Turtles

Abstract: Field and laboratory studies were conducted during 1989—1994 to investigate the overwintering strategies of hatchling turtles representing four families native to western Nebraska. Whereas hatchling snapping turtles (Chelydra serpentina) and spiny soft—shelled turtles (Apalone spinifera) overwinter in aquatic habitats, yellow mud turtles (Kinosternon flavescens) and ornate box turtles (Terrapene ornata) burrow below the natal nest and hibernate in sandy soil. Painted turtles (Chrysemys picta) overwinter within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 37 publications
0
87
2
Order By: Relevance
“…Turtles lay eggs in shallow nests on land, which hatch in late summer or early fall. Snapping turtle hatchlings emerge immediately after hatching and move to water (Congdon et al, 1987;Costanzo et al, 1995Costanzo et al, , 1999, where they spend their first winter submerged. In contrast, map and painted turtle hatchlings remain in the nest, surviving the freezing temperatures of winter via supercooling or freezetolerance, and emerge from the nest the following spring (map turtles: Costanzo et al, 2001b;Pappas et al, 2000;Baker et al, 2003;painted turtles: Packard, 1997;Weisrock and Janzen 1999).…”
Section: G G E O G R a P H Ic A C S E R P E N Ti N A C P Ic Ta mentioning
confidence: 99%
“…Turtles lay eggs in shallow nests on land, which hatch in late summer or early fall. Snapping turtle hatchlings emerge immediately after hatching and move to water (Congdon et al, 1987;Costanzo et al, 1995Costanzo et al, , 1999, where they spend their first winter submerged. In contrast, map and painted turtle hatchlings remain in the nest, surviving the freezing temperatures of winter via supercooling or freezetolerance, and emerge from the nest the following spring (map turtles: Costanzo et al, 2001b;Pappas et al, 2000;Baker et al, 2003;painted turtles: Packard, 1997;Weisrock and Janzen 1999).…”
Section: G G E O G R a P H Ic A C S E R P E N Ti N A C P Ic Ta mentioning
confidence: 99%
“…When turtles were exposed to a high salinity, plasma osmolality and concentrations of Na + , Cl -and urea increased significantly and urea synthesis also increased (Lee et al, 2006). During hibernation plasma osmolality increased, largely due to the retention of urea, in Chrysemis picta (Costanzo et al, 1995). In hatchling turtles, accumulation of urea might be associated with cold hardiness in the winter (Costanzo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For the two former species, it is assumed that if the hatchlings leave the nest, they overwinter aquatically, while for the latter species fall emergence coupled with aquatic or terrestrial overwintering has been reported (Draud et al 2004), as well as overwintering in the nest coupled with fall emergence (Baker et al 2006). Other species have been consistently reported to be overwhelmingly fall emergers, including Snapping Turtles (Chelydra serpentina - Obbard and Brooks 1981;Carroll and Ultsch 2007), Spiny Softshell Turtles (Apalone spinifera - Christiansen and Gallaway 1984;Costanzo et al 1995), Musk Turtles (Sternotherus odoratus Cagle 1942;Mitchell 1988), Wood Turtles (Glyptemys insculpta -Harding 1991;Carroll and Ultsch 2007), Spotted Turtles (Clemmys guttata -Ernst 1976;Carroll and Ultsch 2007), and Blanding's Turtles (Emydoidea blandingii -Standing et al 1997-Standing et al , 1999Pappas et al 2000). Hatchlings of most of these species are assumed to overwinter aquatically, even though some may remain on land for extended periods before entering the water; e.g., Wood Turtles (Tuttle and Carroll 2005;Castellano, Behler, and Ultsch, un pub -lished data) and Blanding's Turtles (Standing et al 1997(Standing et al , 1999.…”
mentioning
confidence: 99%